2016
DOI: 10.2337/db16-0473
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Steroid Sex Hormones and Sex Hormone–Binding Globulin With the Risk of Type 2 Diabetes in Women: A Population-Based Cohort Study and Meta-analysis

Abstract: It remains unclear whether endogenous sex hormones (ESH) are associated with risk of type 2 diabetes (T2D) in women. Data of 3,117 postmenopausal women participants of the Rotterdam Study were analyzed to examine whether ESH and sex hormone-binding globulin (SHBG) were associated with the risk of incident T2D. Additionally, we performed a systematic review and meta-analysis of studies assessing the prospective association of ESH and SHBG with T2D in women. During a median follow-up of 11.1 years, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
76
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 46 publications
13
76
3
3
Order By: Relevance
“…35 The 2018 Endocrine Society Clinical Practice Guideline on testosterone therapy in men with hypogonadism no longer recommend screening men with T2DM for low serum testosterone, and advise against using testosterone therapy to improve glycaemic control. 36 Low circulating SHBG has been consistently identified as a surrogate marker for T2DM in both sexes in a number of smaller studies and meta-analyses, 9,37,38 and our study supports these observations. In a meta-analysis of 13 population-based studies with 1912 incident cases of T2DM, low SHBG was associated with increased risk of T2DM in women, irrespective of menopausal status.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…35 The 2018 Endocrine Society Clinical Practice Guideline on testosterone therapy in men with hypogonadism no longer recommend screening men with T2DM for low serum testosterone, and advise against using testosterone therapy to improve glycaemic control. 36 Low circulating SHBG has been consistently identified as a surrogate marker for T2DM in both sexes in a number of smaller studies and meta-analyses, 9,37,38 and our study supports these observations. In a meta-analysis of 13 population-based studies with 1912 incident cases of T2DM, low SHBG was associated with increased risk of T2DM in women, irrespective of menopausal status.…”
Section: Discussionsupporting
confidence: 84%
“…28 Male androgen deficiency occurs as a consequence of primary testicular pathology, hypothalamic-pituitary disorders, obesity or as part of the ageing process in older men. 37 SHBG levels are typically higher in women, and our data confirm that reduced circulating concentrations are associated with a higher risk of T2DM than that observed in men. 31 Whilst the relationship between obesity and hypogonadism in men is complex and bidirectional, 32 observations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings were consistent with the previous studies which had pointed out that low serum testosterone levels are strongly related to the development of T2DM, and low SHBG and testosterone levels may constitute part of the IFG status of males . At the same time, previous reports demonstrated that testosterone treatment could weaken insulin resistance by increasing the number of lipolysis and beta‐adrenoceptors in male rat adipocyte .…”
Section: Discussionmentioning
confidence: 62%
“…However, no study has examined the role of postmenopausal hormone levels in the association between age of menopause and risk of type 2 diabetes. Although the available evidence is not persuasive and the mechanisms remain unclear, age of menopause might be associated with levels of endogenous sex hormones, which might affect the risk of type 2 diabetes in postmenopausal women [12][13][14][15][16][17]. Therefore, it is not clear whether the observed association between early onset of menopause and risk of type 2 diabetes can be explained by differences in sex hormones levels in women who experience early vs late menopause.…”
Section: Introductionmentioning
confidence: 99%